Effects of Pilates Exercises and Lavender Aromatherapy on Postpartum Women's Fatigue - Agustina Hidayatul Khasanah; Rufidah Maulina; Revi Gama Hatta Novika; Iffah Indri Kusmawati; Noviyati Rahardjo Putri (Journal of Maternal and Child Health, 2025)
Background: Physical and psychological changes during the postpartum period can cause stress and fatigue in mothers that can affect the care of individuals, families, and their babies. The long-term impact of postpartum fatigue is the cessation of lactation, the development of stress, and postpartum depression. Nonpharmacological efforts in the form of pilates exercises and lavender aromatherapy are one of the efforts to reduce fatigue levels in postpartum mothers. This study aimed to determine the effect of pilates exercises and lavender aromatherapy on fatigue in postpartum mothers in the Andong Health Center work area. Subjects and Method: This study was a quasi-experimental, control group pretest-posttest design. The sampling technique used was purposive sampling, and as many as 32 postpartum mothers who experienced fatigue were involved in this study. This study was divided into 2 groups, namely the experimental group with the provision of pilates exercises and lavender aromatherapy, and the control group without treatment as a comparison. The independent variables of this study were pilates exercises and lavender aromatherapy. The dependent variable was postpartum maternal fatigue. The data analysis used is the Wilcoxon test and the Mann-Whitney test. Results: Analysis using the Mann-Whitney statistical test showed significant results with test results (p-value <0.05). From these results, it was found that there was a significant difference in the respondents of the experimental posttest group and the control posttest group.   Conclusion: Pilates exercise and lavender aromatherapy have an effect on the level of fatigue reduction in postpartum mothers in the experimental pretest-posttest group in the Andong Health Center work area. This study is expected to remind all postpartum women to take better care of their physical and mental health, to be able to independently perform Pilates exercises according to the given procedures, and to independently apply the use of lavender aromatherapy.